Company law and corporate finance - Ferran, Eilís (Oxford University Press, 1999)
This book deals with the technicalities of company law within a wider framework that recognizes the importance of market forces and corporate governance and explains issues about corporate finance theory and practice. It identifies the company as a financing vehicle and shows how the law facilitates the raising of finance by providing the corporate form and methods of financing that match the changing needs of a business.